FEAR AVOIDANCE BELIEF FOLLOWING OCCUPATIONAL RELATED INJURIES AMONG AVIATION WORKERS (International Journal of Physiotherapy, 2018)
Background: The growth development of the aviation industry in Malaysia is very encouraging to become a regional aviation center. The commitments from each engage in this industry is vital to ensure its sustainability. Fear avoidance belief is subsequent complication following an occupationally related injury. It will reduce individual performance at the workplace and hinder the positive growth of an industry. Currently, there is limited data available address such issues in Malaysia.Methods: This study is conducted to determine the association of fear avoidance belief following occupationally related injury among aviation workers. This is a cross-sectional study involving individual working in Malaysia aviation industry and sustain an occupationally related injury. The study tools used was the Fear Avoidance Belief Questionnaire (FABQ), which consists of physical related and work-related subscale.Results: Total number of respondents involve is 195 with a mean age of 34 years old, and the majority is male (n = 103). Most of them (31.3%) were baggage & cargo handler work category. Their work natures are varied, 37.9% were engaged with a visual display unit. There is a moderately strong association of fear avoidance belief (φc =0.26 & 0.28) between physically related subscale with respondents work categories and work nature respectively (P < 0.05).Conclusion: The fear avoidance belief among respondents exists and cannot be denied. Preventive method of enhancing self-empowerment through education and training is the effective mean in generating self-care at a workplace.